Methods of testing of program modules of flight information processing - Райчев, И. Э.; Харченко, А. Г.; Яцков, Н. А. (Proceedings of National Aviation University (archive), 2000)
Considered are the problems of testing modules included in the structure of flight monitoring complexes. Presented is the analysis of flight monitoring complexes and the substantiated choice of methods which can be applied for their testing, also given are recommendations as to application of each method for testing of program modules. Developed is a complex strategy of constructing tests for modules of flight information processing. Investigated are practical ways of testing functional groups of modules of flight data processing